Virus-like particle-based vaccines against hepatitis C virus infection. (February 2013) - Bellier, Bertrand; Klatzmann, David
HCV infection is a worldwide health problem and much effort is being made to develop novel therapies. New vaccines are designed for preventive and therapeutic use through induction of robust immunity, including neutralizing antibodies and T-cell-mediated immunity. Novel future vaccine approaches include virus-like particle (VLP)-based vaccines that have been successfully employed to prevent infections by hepatitis B virus or human papillomavirus. The HCV-derived VLP approach simplifies the delivery of neutralizing antibody- and core-specific T-cell epitopes in a highly immunogenic single construct resembling mature HCV virions. The size, particulate nature and dense, repetitive structure of VLPs are the basis for their innate immunogenicity. Consequently, VLPs have also been exploited as antigenic platforms. Association of HCV antigens with heterologous structural viral proteins able to form recombinant VLPs (HBsAg, HBcAg, MLV Gag, PapMV coat protein) is also a promising approach for induction of HCV-specific immune responses. This article summarizes the different VLP-based vaccine approaches that are currently under development.